'When there is love between a father and mother, the child will also be loved': a qualitative exploration of the links between couples' relationships, parenting and early childhood development in Mwanza, Tanzania - Alya Alsager; Alina Bhojani; Julieth Joseph (BMJ Publishing Group, 2023)
Introduction The relationship between parents is a key component of the family system that is associated with various child outcomes. However, less is known about how caregivers and community members make meaning of the influence of couples' relationships on child outcomes and to what extent family caregiving processes underlie these links in low-income and middle-income countries. We therefore aimed to qualitatively investigate the pathways through which positive and negative couples' relationship dynamics influence early child development.Methods In June 2022, we conducted 60 in-depth interviews (29 fathers and 23 mothers and 8 community stakeholders) and 9 focus group discussions (3 with fathers only, 2 with mothers only and 4 mixed parent groups) from across four purposively sampled communities in Mwanza, Tanzania. We analysed data using elements of thematic content analysis and a grounded theory methodology.Results We identified five main mechanisms through which couples' relationships influenced early child outcomes, including child emotional well-being, health, nutrition and development: (1) parents' nurturing care practices, (2) parental violence against children, (3) parent-child bonding, (4) parental mental health and (5) child indirect exposures through witnessing interparental relationships. Many of these pathways were interconnected and shaped by gender norms.Conclusions Our results highlight the importance of engaging couples and targeting marital relationship dynamics as part of caregiving interventions that aim to improve early child outcomes. Strengthening family caregiving relationships between mothers, fathers, and each with their children is crucial for promoting early childhood development.